The secret doctrine of the Jews: Jewish theosophists and the Kabbalah - Hus, Boʿaz (Suny series in western esoteric traditions, 2025)
"A comprehensive exploration of the Jewish adherents of the Theosophical Society and their impact on modern Jewish culture and the development of modern forms of Kabbalah"--